Mortmain Hall - Edwards, Martin, 1955- (A Rachel Savernake Golden Age mystery, 2020)
"Journalist Jacob Flint finds himself framed for murder after a surprise witness helps a man accused of a "blazing car" killing escape the gallows. To save himself, Jacob needs to discover what links these strange events to a remote estate on a northern coast, Mortmain Hall. But the house party culminates in tragedy when a body is found beneath the crumbling cliffs. Rachel Savernake, who's been invited to the party, proposes an intricate-and dangerous-solution to the assembled guests. Will her relentless quest for the truth bring down the British establishment?"--